Usulan Rancangan Fasilitas Kerja dengan Pendekatan Analisis Postur Kerja pada Pekerja Las (Studi Kasus pada CV. Primayasa – Semarang) - Hara Nawawi; Purnawan Adi Wicaksono (Industrial Engineering Online Journal, 2012)
CV. Primayasa is one of the trusted company for machinery improvement project of sugar factories PTPN IX (PT Perkebunan Nusantara IX) in Central Java. In this place there is not ergonomic working posture is when the welding process. The results show that the Nordic Body Map welding workers experiencing pain in multiple body segments. The research starts from analyzing the causes of pain in welding workers CV Primayasa through posture analysis. Based on the results of research conducted on posture welding worker CV Primayasa at the welding process prior to the proposed design of the facility shows that have a risk posture musculoskeletal disorders. This is what causes the pain complaints of the welding workers CV Primayasa. Indications of the risk of musculoskeletal disorders can be seen from the following research results, there is a spinal compression force exceeds the normal limit that is equal to 4152.362 N, there is a grand score RULA reached number 7, which means being in a high level in terms of the risk of musculoskeletal disorders, and there is the cumulative score ManTRA tool v 2.0 in a particular body segment which reached number 15. On a cumulative score spell if making 15 or more, then it indicates that the segment of the body at risk of musculoskeletal disorders. To reduce the risk of musculoskeletal disorders researchers propose the design of work facilities in the form of tables and chairs that can be used to work in a standing position or in a sitting position. The design of this facility would work by looking at the consideration of the posture analysis and anthropometric welding workers CV Primayasa. The evaluation of the proposed facility design work on this study shows a decrease in the level of risk of musculoskeletal disorders was used either sitting or standing position. The results of this study was the entire spinal compression forces were under normal limits 3500 N, RULA grand score only reached number 3 and 4, and all the cumulative score ManTRA tool v 2.0 is under the number 15. The results of these studies indicate that use of the proposed design of the new facility is safe enough to use for work